Characteristics of Fossil Wood from Loa Tebu Kutai Kertanegara, East Kalimantan - Nani Husien; Muhammad Nur Hidayat; Agus Sulistyo Budi; Erwin (Jurnal Multidisiplin Madani, 2023)
Fossil Wood is wood that has petrified as a result of wood or plant stems being buried by sediment, does not experience decay and the cells in the wood are replaced by minerals over a long period of time but the outer structure of the wood is still maintained. One way to find out the characteristics of fossil wood is by observing or characterizing it both macroscopically and microscopically. This study aims to determine the macroscopic characteristics, hardness values and density of wood fossils found in Loa Tebu Village, Kutai Ketanegara. Observations of macroscopic characteristics included the color of wood fossils which were observed by naked eye and with a loupe magnification of 10x, and observations of other macroscopic characteristics were carried out on three areas of wood namely transverse, tangential and radial planes using a Nikon SMZ 645 Stereo Microscope with a magnification of 30x. The hardness value uses a rock hardness test tool, namely "Diamond Selector II", while the density uses the general calculation standard for specific gravity, namely the ratio of mass to volume. The results showed that the characteristics of the fossil wood from Loa Tebu were light brown, dark brown, white and gray in color. The color found in the wood fossils is probably caused by cells that have been mixed with inorganic elements and mineral constituents around the location of the wood fossils. Another macroscopic structural observation was the discovery of wood cells such as those of broad leaf wood in general, namely the presence of vessel cells (pores), radius cells and clusters of fiber cells. Axial intercellular channels (SIA) were also found in the samples and arranged tangentially. The AIA characteristics found here are common characteristics that are often found in several species of wood from the Dipterocarpaceae family. The results of the measurement of the sample hardness value were 4 on the Mohs scale and the density was 3.26